Towards an architectural history of Kilwinning Abbey (Proceedings of the Society of Antiquaries of Scotland, 1996)
An attempt to chronicle the Tironensian Abbey's construction -- particularly that of the church. `Appendix 1: the area between the south gable and the chapter-house' (864--6), and `Appendix 2: the south-west stair turret of the transept' (866--8) conclude proceedings.